Bis-polyethylene glycol-functionalized imidazolium ionic liquids: A multi-method approach towards bulk and surface properties - Seidl, Vera; Bosch, Michael; Paap, Ulrike; Livraghi, Mattia; Zhai, Ziwen; Wick, Christian; Koller, Thomas Manfred; Wasserscheid, Peter; Maier, Florian; Smith, Ana-Suncana; Bachmann, Julien; Steinrück, Hans-Peter; et al. (Journal of Ionic Liquids, 2022)
Adding to the versatile class of ionic liquids, we report a new series of hydrophilic polyethylene glycol-functionalized room-temperature ionic liquids, offering interesting thermo- and electrochemical behavior as well as remarkable surface properties. A scalable and generally applicable synthetic procedure for the preparation of N,N’-bis(polyethylene glycol)imidazolium salts, generally abbreviated as [(mPEGn)2Im][A] (n = 2‒6, A = I‒, OMs‒, PF6‒, NTf2‒) was developed. These ionic liquids were studied concerning their thermo- and electrochemical properties, such as phase transition behavior, decomposition temperature, viscosity, and density, as well as electrical conductivity and electrochemical stability, using i.a. differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), electrochemical impedance spectroscopy (EIS) and linear sweep voltammetry (LSV). Additionally, the surface properties were investigated by angle-resolved X-ray photoelectron spectroscopy (ARXPS) and the pendant drop method. olecular dynamics simulations complement the studies and provide insight into the molecular structure of the ionic liquids and their specific orientation at the liquid-vacuum interface.<br

Continuous, crystalline Sb2S3 ultrathin light absorber coatings in solar cells based on photonic concentric p-i-n heterojunctions - Büttner, Pascal; Scheler, Florian; Döhler, Dirk; Barr, Maissa; Bosch, Michael; Rey, Marcel; Yokosawa, Tadahiro; Hinz, Sandra; Maultzsch, Janina; Spiecker, Erdmann; Vogel, Nicolas; Minguez Bacho, Ignacio; et al. (Nano Energy, 2022)
Many modern types of solar cells that rely exclusively on earth-abundant non-toxic materials include interfaces between a heavier metal chalcogenide and another type of semiconductor. Often, the chemical (adhesion) and physical (charge transfer) characteristics of those interfaces are the defining factors for the final device performance. Here, we describe that a ZnS adhesion layer is not sufficient to prevent the dewetting of Sb2S3 upon annealing a thin layer of it on an oxidic surface if the substrate is not planar and features highly curved surfaces. An ALD-coated sacrificial capping layer of ZnO prevents the morphological rearrangements of Sb2S3 during thermal crystallization and can be removed subsequently. When implemented towards a photovoltaic p-i-n heterojunction, this strategy furnishes perfect conformality of the layer stack but unsatisfactory performance. The correlation of interface chemistry with the electrical properties and the device performance identifies a reducing effect of ZnO atomic layer deposition chemistry on the Sb2S3 surface as the cause of Zn diffusion into the light absorbing semiconductor. This deleterious doping can be prevented by a preliminary oxidative treatment of the Sb2S3 surface with ozone. When applied to a structured substrate consisting of ordered arrays of nanospheres, this approach yields the first ever concentric p-i-n heterojunction solar cells with photonic light trapping effect—a geometry which in comparison with standard scattering layers'on top’ inherently generates a very large refractive index contrast. In the red part of the visible spectrum, light absorption amounts to the value expected with four passes through a planar layer of the thickness used here (35 nm Sb2S3). This effect allows us to demonstrate >5% overall solar energy conversion efficiency with only 35 nm of a simple light absorber phase that uses no toxic, rare materials
CRIS-Team Scopus Importer:2022-10-14
Keywords: Atomic layer deposition; Concentric semiconductor junctions; Antimony chalcogenides; Interfacial layers; Photonic structures; Gradient doping; Interface chemistry

Electrochemically controlled energy release from a norbornadiene-based solar thermal fuel: increasing the reversibility to 99.8% using HOPG as the electrode material - Waidhas, Fabian; Jevric, Martyn; Bosch, Michael; Yang, Tian; Franz, Evanie; Liu, Zhi; Bachmann, Julien; Moth-Poulsen, Kasper; Brummel, Olaf; Libuda, Jörg (Journal of Materials Chemistry A, 2020)
Solar energy conversion using molecular photoswitches holds great potential to store energy from sunlight in the form of chemical energy in a process that can be easily implemented in a direct solar energy storage device. In this context, we investigated the electrochemically triggered energy release of a solar thermal fuel based on the norbornadiene (NBD)/quadricyclane (QC) couple by photoelectrochemical IR reflection absorption spectroscopy (PEC-IRRAS). We studied the photo-induced conversion of the energy-lean 2-cyano-3-(3,4-dimethoxyphenyl)-norbornadiene (NBD ') to the energy-rich 2-cyano-3-(3,4-dimethoxyphenyl)-quadricyclane (QC ') and the electrochemically triggered reconversion using highly oriented pyrolytic graphite (HOPG) as an electrode material. We compared our results with the results obtained previously using Pt(111) electrodes and we characterized the photochemical and electrochemical properties of the storage system. NBD ' can be photochemically converted and electrochemically reconverted with very high selectivity. HOPG largely suppresses the unwanted catalytic reconversion which was observed on Pt(111). We performed repetitive cycling experiments for 1000 cycles to determine the reversibility of the system. Our results show that it is possible to reach reversibility above 99.8% using HOPG as an electrode material.
CRIS-Team WoS Importer:2020-09-04

Stability of Bimetallic PtxRuy - From Model Surfaces to Nanoparticulate Electrocatalysts - Kormanyos, Attila; Büttner, Pascal; Bosch, Michael; Minichova, Maria; Körner, Andreas; Jenewein, Ken J.; Hutzler, Andreas; Mayrhofer, Karl J.J.; Bachmann, Julien; Cherevko, Serhiy (ACS Materials Au, 2024)
Fundamental research campaigns in electrocatalysis often involve the use of model systems, such as single crystals or magnetron-sputtered thin films (single metals or metal alloys). The downsides of these approaches are that oftentimes only a limited number of compositions are picked and tested (guided by chemical intuition) and that the validity of trends is not verified under operating conditions typically present in real devices. These together can lead to deficient conclusions, hampering the direct application of newly discovered systems in real devices. In this contribution, the stability of magnetron-sputtered bimetallic PtxRuy thin film electrocatalysts (0 at. % to 100 at. % Ru content) along with three commercially available carbon-supported counterparts (50-67 at. % Ru content) was mapped under electrocatalytic conditions in acidic electrolytes using online ICP-MS. We found several differences between the two systems in the amount of metals dissolved along with the development of the morphology and composition. While the Pt-rich PtxRuy compositions remained unchanged, 30-50 nm diameter surface pits were detected in the case of the Ru-rich sputtered thin films. Contrastingly, the surface of the carbon-supported NPs enriched in Pt accompanied by the leaching of a significant amount of Ru from the alloy structure was observed. Change in morphology was accompanied by a mass loss reaching around 1-2 wt % in the case of the sputtered samples and almost 10 wt % for the NPs. Since PtxRuy has prime importance in driving alcohol oxidation reactions, the stability of all investigated alloys was screened in the presence of isopropanol. While Pt dissolution was marginally affected by the presence of isopropanol, several times higher Ru dissolution was detected, especially in the case of the Ru-rich compositions. Our results underline that trends in terms of electrocatalytic activity and stability cannot always be transferred from model samples to systems that are closer to the ones applied in real devices.
CRIS-Team Scopus Importer:2024-05-24
Keywords: bimetallic electrocatalyst; dealloying; electrocatalyst stability; material library; online ICP-MS

Ultrafast electronic relaxation pathways of the molecular photoswitch quadricyclane - Borne, Kurtis D.; Cooper, Joseph C.; Ashfold, Michael N. R.; Bachmann, Julien; Bhattacharyya, Surjendu; Boll, Rebecca; Bonanomi, Matteo; Bosch, Michael; Callegari, Carlo; Centurion, Martin; Coreno, Marcello; Curchod, Basile F. E.; et al. (Nature Chemistry, 2024)
The light-induced ultrafast switching between molecular isomers norbornadiene and quadricyclane can reversibly store and release a substantial amount of chemical energy. Prior work observed signatures of ultrafast molecular dynamics in both isomers upon ultraviolet excitation but could not follow the electronic relaxation all the way back to the ground state experimentally. Here we study the electronic relaxation of quadricyclane after exciting in the ultraviolet (201 nanometres) using time-resolved gas-phase extreme ultraviolet photoelectron spectroscopy combined with non-adiabatic molecular dynamics simulations. We identify two competing pathways by which electronically excited quadricyclane molecules relax to the electronic ground state. The fast pathway (<100 femtoseconds) is distinguished by effective coupling to valence electronic states, while the slow pathway involves initial motions across Rydberg states and takes several hundred femtoseconds. Both pathways facilitate interconversion between the two isomers, albeit on different timescales, and we predict that the branching ratio of norbornadiene/quadricyclane products immediately after returning to the electronic ground state is approximately 3:2.<br
Keywords: Chemical physics; Photochemistry

Valence shell electronically excited states of norbornadiene and quadricyclane - Cooper, Joseph C.; Holland, David M. P.; Ingle, Rebecca A.; Bonanomi, Matteo; Faccialà, Davide; De Oliveira, Nelson; Abid, Abdul R.; Bachmann, Julien; Bhattacharyya, Surjendu; Borne, Kurtis D.; Bosch, Michael; Centurion, Martin; et al. (Journal of Chemical Physics, 2024)
The absolute photoabsorption cross sections of norbornadiene (NBD) and quadricyclane (QC), two isomers with chemical formula C7H8 that are attracting much interest for solar energy storage applications, have been measured from threshold up to 10.8 eV using the Fourier transform spectrometer at the SOLEIL synchrotron radiation facility. The absorption spectrum of NBD exhibits some sharp structure associated with transitions into Rydberg states, superimposed on several broad bands attributable to valence excitations. Sharp structure, although less pronounced, also appears in the absorption spectrum of QC. Assignments have been proposed for some of the absorption bands using calculated vertical transition energies and oscillator strengths for the electronically excited states of NBD and QC. Natural transition orbitals indicate that some of the electronically excited states in NBD have a mixed Rydberg/valence character, whereas the first ten excited singlet states in QC are all predominantly Rydberg in the vertical region. In NBD, a comparison between the vibrational structure observed in the experimental 11B1–11A1 (3sa1 ← 5b1) band and that predicted by Franck–Condon and Herzberg–Teller modeling has necessitated a revision of the band origin and of the vibrational assignments proposed previously. Similar comparisons have encouraged a revision of the adiabatic first ionization energy of NBD. Simulations of the vibrational structure due to excitation from the 5b2 orbital in QC into 3p and 3d Rydberg states have allowed tentative assignments to be proposed for the complex structure observed in the absorption bands between ∼5.4 and 7.0 eV.<br
Keywords: Photoabsorption; Synchrotron radiation; Ions and properties; Isomerism; Absorption spectroscopy; Oscillator strengths; Organic compounds; Chemical compounds; Absorption band; Rydberg states